Eating behavior disordes of female adolescents - Burgić-Radmanović, Marija (Array, 2009)
Adolescence is a period of significant physical, emotional and intellectual changes, as well as changes in social roles, relations and expectations. Survey questionnaire (16 questions) is a scale for self-rating of eating disorders designed by the author. Response rate was 389 out of 419 (92.8%). Results: Eight point seven per cent of the female adolescents had a Body Mass Index (BMI) less than 18.5. About 2/3 adolescents are not satisfied with their figure. One-half of the adolescents are terrified of increasing their weight. This research indicates the necessity of education of adolescents and developing prevention programs to help them to adopt healthier nutrition and lifestyle in early life. One-third (1/3) of adolescents accept themselves whether thin or obese, while about 43% adolescents are sometimes or often terrified about being overweight. One-half of adolescents are terrified by increase in weight